The Effect of Remuneration, Work Environment and Employee Competence on Employee Performance at Pattimura University Ambon - Muhammad Bugis; Zainuddin Latucosina (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
In improving employee performance at Pattimura University, efforts that can be taken include providing adequate remuneration, creating a harmonious work environment and then employee competence is maintained. With this effort, it is hoped that the performance of employees at Pattimura University can be improved. This study aims to analyze the effect of remuneration, work environment and employee competence on employee performance at Pattimura University. The data analysis method used is Partial Least Squares (PLS) to analyze the effect of remuneration, work environment and employee competence on employee performance. The sample of this study was permanent employees working at Pattimura University. The results showed that Remuneration did not have a positive effect on employee performance. The work environment has a positive effect on employee performance. And employee competence has a positive effect on employee performance.